2005
DOI: 10.1002/bjs.4937
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of non-sentinel lymph node status in breast cancer with a micrometastatic sentinel node

Abstract: Size of micrometastasis and presence of lymphovascular invasion were significantly related to the risk of finding additional positive axillary lymph nodes when the SN contained only micrometastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 34 publications
4
22
0
3
Order By: Relevance
“…In our study, 1 of 2 patients with isolated tumor cells, and 5 of 14 patients with micrometastases had non-SN involvement (p=0.312). There are also studies that have investigated patients in whom ALND was not performed after finding micrometastasis in SNs, and they did not find any significant difference between patients, in terms of prognosis (30,31). However, because up to 53% of patients with micrometastasis in SNs have non-SN metastasis, it is emphasized by van Deurzen et al, that macrometastases may arise in non-SNs of patients with micrometastasis or even isolated tumor cells in SNs (22).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 1 of 2 patients with isolated tumor cells, and 5 of 14 patients with micrometastases had non-SN involvement (p=0.312). There are also studies that have investigated patients in whom ALND was not performed after finding micrometastasis in SNs, and they did not find any significant difference between patients, in terms of prognosis (30,31). However, because up to 53% of patients with micrometastasis in SNs have non-SN metastasis, it is emphasized by van Deurzen et al, that macrometastases may arise in non-SNs of patients with micrometastasis or even isolated tumor cells in SNs (22).…”
Section: Discussionmentioning
confidence: 99%
“…These authors concluded that, in such circumstances, it would be possible to avoid axillary clearance, but that prospective randomized studies would answer this question better. 15 Today, since there is no difference in survival or distant recurrence, the choice between breast-conserving therapy with axillary dissection and modified radical mastectomy should depend on patient preference when appropriate. 13 A less invasive method of axillary evaluation is very appealing, given the potential morbidity associated with axillary dissection.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this, Leidenius et al [46] found 25% of patients with SLN MM to have residual disease in the axilla. Schrenk et al [47] have compared patients with SLN MM to those with SLN macrometastases undergoing ALND. Non-SLNs were found to be positive in 18% of those with SLN MM compared to 51.1% of those with macrometastasis.…”
Section: Analysis Of the Sentinel Lymph Nodementioning
confidence: 99%